USING ALTERNATIVE ASSESSMENT TECHNOLOGIES TO PROMOTE ACTIVE LEARNING - MANUKYAN, ANI (IJRDO- Journal of Educational Research, 2017)
The author tries to define alternative assessment as an act of acquiring and analyzing information about students for a purpose, identifying and diagnosing the special educational needs of education and informing planning for further actions. It forms an integral part of the process of providing support and educational wherewithal. This information includes knowledge about an individual’s personality, way of thinking and style of learning, as well as it helps to discover his/her cognitive abilities, environmental status, academic achievement and social competence. In this paper we consider each type of assessment, highlight the relative strengths and weaknesses of each one, and discuss how teachers can choose among many options with two primary considerations: the importance of the effect and the crucial need to use multiple sources of information. The article also dwells on the effective ways of developing alternative assessment to promote active learning. Our next step is the sharing of the results of the survey methods we consider particularly productive in assessing alternatively. To reach our aims we organized a range of experimental lessons, conducted surveys with questionnaires and organized a debate to prove that set of activities chosen by us can enrich and reinforce the students’ comprehension of alternative assessment, as well as it can stimulate the usage of alternative assessment in the practice of teachers